Evaluation of coffee bean husk fermented by a combination of Aspergillus niger, Trichoderma harzianum, and Saccharomyces cerevisiae as animal feed - Himmatul Khasanah; Desy Cahya Widianingrum; Listya Purnamasari; Ali Wafa; Seong-Gu Hwang (Jurnal Ilmu-Ilmu Peternakan, 2022)
Abundant coffee bean husk acquires an alternative source of fiber for livestock feed, but a high level of the crude fiber of it became an obstacle. Solid-state fermentation technology using lignocellulolytic fungi is known to be able to improve the nutritional quality of feedstuff that have high fiber content. Its mechanism is through the degradation of the lignocellulose fraction and enhance protein content. This study aimed to determine the nutritional quality of fermented coffee bean husk with a combination of fungi and yeast. The fermentation method used a solid-state fermentation consisting of 7 different inoculums, namely: P0: Unfermented coffee bean husk, P1: Aspergillus niger, P2: Saccharomyces cerevisiae, P3: Trichoderma harzianum, P4: Aspergillus niger + S. Cereviciase, P5: Aspergillus niger + Trichoderma harzianum, P6: Saccharomyces cerevisiae + Trichoderma harzianum and P7: Aspergillus niger + Saccharomyces. Cereviciase + Trichoderma harzianum. The nutritional quality of the fermented coffee bean husk was determined by proximate analysis, lignocellulolytic fraction, and digestibility. The data obtained were analyzed by ANOVA and followed by Tukey's post hoc test. The crude fiber content of fermented coffee bean husk (P1-P7) was lower than unfermented (P0). There was no significant difference among treatments in crude fat and protein. Treatment P3 has the highest total digestibility nutrient (70) and the lower crude fiber (15.03). A combination of Aspergillus niger and Saccharomyces cerevisiae reduce lignin content by about (4,16%). In conclusion, the fermented coffee bean husk can be utilized as animal feedstuff with higher nutritional quality than unfermented.